(untitled) (The International Journal for Scientific Research, 2023)
This study deals with the impact of Jewish Orientalism and its manifestations in the modern Arabic linguistic study, understanding its danger, especially since it was built, for the most part, on political, religious, or other foundations that distance it from science and objectivity to a great extent. The importance of this study lies in calling for a re-reading of the Orientalist output that invaded linguistic studies, a balanced and careful reading, far from influence and fascination, far from isolation and disapproval, in order to capture what is compatible with the Arab cultural identity, and what its mechanisms are suitable for enriching knowledge, revealing the patterns and aesthetics of the Arab heritage. As well as taking serious and clear critical positions on Orientalist approaches, based on cognitive foundations. Especially since those approaches that continued to benefit from other Oriental outputs with their terminology. Some Arab critics in the cultural arena continued to reproduce them, making them a field for application. This study follows the inductive analytical approach, which is based on tracking different opinions about Jewish Orientalism, its problems, its characteristics, its use in serving Jewish purposes, and its danger. This study reassured that any Jewish researcher could prefer to work within the Orientalist movement as a European Orientalist, and not as a Jewish one. They greatly benefited from it in serving their Zionist issues by presenting them in a Western form, to ensure their acceptance among Arabs and Muslims, taking advantage of the Eastern inferiority complex towards the West. As for the Arab modern scholars, their linguistic study ranged between a study largely influenced by what they learned from the West under the slogan of modernity, science and objectivity; it began to be read through the eyes of the Orientalists. And on the other side, a study that relied on a cultural reference represented in preserving and protecting Arabic from malicious calls. Another method represented in following the linguistic theories developed by the West in its own context, based on combining the borrowed approach with the Arabic subject in addition to a study represented in investing the outcome of accumulated efforts, to form a scientific awareness of Arabic and a general linguistic one, in which Arabic raises its own questions and issues.